Multisensory cueing facilitates naming in aphasia - Klaudia Grechuta; Belén Rubio Ballester; Rosa Espín Munné; Teresa Usabiaga Bernal; Begoña Molina Hervás; Bettina Mohr; Friedemann Pulvermüller; Rosa Maria San Segundo; Paul F. M. J. Verschure (Journal of NeuroEngineering and Rehabilitation, 2020)
Abstract Background Impaired naming is a ubiquitous symptom in all types of aphasia, which often adversely impacts independence, quality of life, and recovery of affected individuals. Previous research has demonstrated that naming can be facilitated by phonological and semantic cueing strategies that are largely incorporated into the treatment of anomic disturbances. Beneficial effects of cueing, whereby naming becomes faster and more accurate, are often attributed to the priming mechanisms occurring within the distributed language network. Objective We proposed and explored two novel cueing techniques: (1) Silent Visuomotor Cues (SVC), which provided articulatory information of target words presented in the form of silent videos, and (2) Semantic Auditory Cues (SAC), which consisted of acoustic information semantically relevant to target words (ringing for “telephone”). Grounded in neurophysiological evidence, we hypothesized that both SVC and SAC might aid communicative effectiveness possibly by triggering activity in perceptual and semantic language regions, respectively. Methods Ten participants with chronic non-fluent aphasia were recruited for a longitudinal clinical intervention. Participants were split into dyads (i.e., five pairs of two participants) and required to engage in a turn-based peer-to-peer language game using the Rehabilitation Gaming System for aphasia (RGSa). The objective of the RGSa sessions was to practice communicative acts, such as making a request. We administered SVCs and SACs in a pseudorandomized manner at the moment when the active player selected the object to be requested from the interlocutor. For the analysis, we compared the times from selection to the reception of the desired object between cued and non-cued trials. Results Naming accuracy, as measured by a standard clinical scale, significantly improved for all stimuli at each evaluation point, including the follow-up. Moreover, the results yielded beneficial effects of both SVC and SAC cues on word naming, especially at the early intervention sessions when the exposure to the target lexicon was infrequent. Conclusions This study supports the efficacy of the proposed cueing strategies which could be integrated into the clinic or mobile technology to aid naming even at the chronic stages of aphasia. These findings are consistent with sensorimotor accounts of language processing, suggesting a coupling between language, motor, and semantic brain regions. Trial registration NCT02928822 . Registered 30 May 2016.